Reading Between Texts: Thai Postgraduate Students' Intertextual Framing and Metacognition Use in Reading - Bell, Joyce (The Reading Matrix, 2008)
Many factors influence students’ reading practices. In the case of international students, home country educational practices and socio-cultural factors may pose a greater influence than for local students. This study reported here, part of a larger study, investigated the intertextual framing practices used in reading by a cohort of Thai postgraduate students in their first and third semesters at an Australian university and their self knowledge of these practices. An ethnographic approach was used incorporating individual interviews and pair think-aloud protocols. In addition, interviews were conducted with postgraduate students at a Thai university to provide further explanation of Thai postgraduate reading practices. It was found that there were significant changes between firs t and third semesters as the students accommodated to the new cultural environment and the requirements of their studies. These changes were facilitating the amount and kind of reading they were required to interpret and evaluate.